Carbon sink strength of a Mediterranean cork oak understorey: how do semi-deciduous and evergreen shrubs face summer drought? - Correia, A. C.; Costa e Silva, F.; Correia, A. V.; Hussain, M. Z.; Rodrigues, A. D.; David, J. S.; Pereira, J. S. (Journal of Vegetation Science, 2013)
Questions How do semi-deciduous and evergreen shrubs exploit environmental resources during summer drought? What is the contribution of the understorey shrubby layer to ecosystem carbon assimilation? To what extent are carbon balance and transpiration impacted by a rain pulse? Location Cork oak open woodland in the Mediterranean region. Methods We used closed dynamic light and dark chambers to measure gas exchange (CO2 and H2O) in the dominant shrub understorey species Cistus salviifolius, Cistus crispus (semi-deciduous) and Ulex airensis (evergreen), together with plant physiological and morphological measurements during summer drought and autumn recovery. A hyperbolic light response model constrained by vapour pressure deficits was fitted for up-scaling shrub photosynthesis to the ecosystem level. The data were compared, on a daily and daytime basis, with gross primary productivity estimates from ecosystem eddy-covariance flux measurements. Results The onset of summer drought led to a significant leaf area reduction in semi-deciduous species. A general decrease in photosynthesis in all species was observed, while evapotranspiration and above-ground respiration fluxes contrasted among species during summer progression and autumn recovery. The shallow-rooted C. salviifolius was able to use light more efficiently than the other two species, although with poor stomatal control over water loss and consistently higher above-ground respiration rates, leading to lower water and carbon use efficiencies when compared with C. crispus. The deep-rooted shrub U. airensis maintained higher leaf water potentials and very low photosynthetic rates while decreasing transpiration rates throughout the summer drought. A summer rain pulse showed that shallow-rooted shrubs use water in an opportunistic way, with immediate leaf rehydration and concomitant photosynthesis increments. Conversely, deep-rooted shrubs (U. airensis) were unresponsive, only recovering photosynthesis with high soil water content. An opportunistic growth response may be disadvantageous to shallow-rooted shrubs in a future climate with extended dry summers and higher probability of rain pulse events. The prominent increase in transpiration rates and plant respiration costs observed during the dry conditions that followed the rain pulse, led to a reduced plant ability to recover after autumn rains. Conclusions The shrubs that naturaly colonized this montado understorey showed contrasting strategies to overcome summer drought, suggesting an efficient mosaic exploitation of seasonal environmental resources. The contribution of these shrubs to total ecosystem CO2 uptake during summer and autumn recovery was 17%. This high contribution implies that shrub density management decisions should consider a carbon balance perspective.
Keywords: Cistus sp; CO2; Eddy-covariance; H2O; Mediterranean; partitioning; Shrubs; Ulex sp; up-scaling

Assessment and up-scaling of CO2 exchange by patches of the herbaceous vegetation mosaic in a Portuguese cork oak woodland - Li, Yue-Lin; Tenhunen, J.; Mirzaei, H.; Hussain, M. Z.; Siebicke, L.; Foken, T.; Otieno, D.; Schmidt, M.; Ribeiro, N.; Aires, L.; Pio, C.; Banza, J.; et al. (Agricultural and Forest Meteorology, 2008)
Long-term eddy covariance measurements over a montado oak woodland in southern Portugal have documented a vulnerability to predicted decreases in springtime rainfall, since water availability during spring limits annual CO2 gain, the growth of fodder for animals, and the production of cork by Quercus suber. The current study examined CO2 exchange of three different herbaceous vegetation components distributed over montado landscapes and within the footprint of long-term landscape eddy covariance monitoring studies. Simultaneous measurements with eddy covariance at two sites and with manually operated chambers at multiple locations revealed that slow drainage of shallow basins, the onset of drying at higher sites and a high release of CO2 below tree canopies signiﬁcantly inﬂuenced the overall course of montado ecosystem gas exchange during the spring. Hyperbolic light response models were employed to up-scale and compare herbaceous gas exchange with landscape net ecosystem CO2 ﬂux. The up-scaling demonstrates the importance of the herbaceous understory in determining annual carbon balance of the montado and suggests a relatively small additional CO2 uptake by the tree canopies and boles, i.e., by the aboveground tree compartment, during springtime. Annual ﬂux totals obtained during the extremely dry year 2005 and a normal precipitation year 2006 for the oak woodland and a nearby grassland were essentially the same, indicating that both ecosystems similarly exploit available resources. Based on comparisons with additional temperate grasslands, we can visualize the montado herbaceous cover as a typical European grassland canopy, but where temperature ﬂuctuations in winter control uptake, and where total production depends on springtime rainfall as it controls phenological events and eventually dieback of the vegetation. On the other hand, tree canopies remain active longer during late spring and early summer, modifying the montado response from that of grassland. Uncertainties in ﬂux estimates via both chamber and eddy covariance methodologies currently prevent a full understanding of vegetation/atmosphere coupling, of the recycling of CO2 between the understory communities and trees, and of relationships between exchange rates of individual components of the vegetation mosaic and overall carbon and water balances in montado landscapes.
Keywords: Herbaceous vegetation; Light response model; montado; net ecosystem exchange; Oak woodland; up-scaling